Profiling and estimation of potential markets for hybrid forages in East Africa - Junca Paredes, Jhon Jairo; Karimi, Peggy; Flórez, Jesús Fernando; Enciso Valencia, Karen Johanna; Hernández, Luis Miguel; Triana Ángel, Natalia; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
East Africa has a significant dairy herd. At the country level in 2020, South Sudan had the highest number of dairy cattle on the African continent with 8,432,559 head with Ethiopia at third (7,556,402 head), Tanzania at fourth (7,116,771 head), and Kenya at sixth (5,112,340 head) rank. In the region, smallholder productive systems predominate making it very difficult to maintain a cow and its calf. Climatic conditions and arid soils exacerbate these challenges as they influence both forage growth and animal performance. These limitations are of great relevance since the sector is essential for food security and the livelihoods of impoverished rural families. Improved forages developed by CIAT, such as the interspecific hybrid Urochloa cv. Mulato II, have shown good results in countries like Kenya and Ethiopia, viz. higher productivity and nutritional quality when compared to traditional materials used in the region, such as Napier and Rhodes grass, and contribute to environmental sustainability. However, their adoption is low, due limited availability of information and extension, problems with the access to finance, and shortages of forage seeds, among others, and they are still susceptible to regional pests such as Red Spider Mite (Tetranychus urticae). Against this background, the CIAT forage breeding program is developing new hybrids adapted to the African environment and pilot tests show promising results. The objective of this document is to estimate the potential market for new interspecific hybrids of Urochloa and potential hybrids of Guinea grass (Megathyrsus maximus) in Ethiopia, Tanzania, Kenya, South Sudan, and Uganda. Specifically, the authors seek to identify the market size (hectares) and commercial values for these new hybrids. The empirical evaluation was carried out with information from FAO consulted in 2022 and regional geographic profiling studies from previous studies. Expert opinions were used to estimate the productivity and potential performance of new hybrids. The results show a potential market of 352,158 ha for new Urochloa interspecific hybrids, corresponding to a market value of US$ 62,479,997. The most representative countries are Ethiopia, Tanzania, and Kenya, which participate with 31.72%, 29.87%, and 21.46%, respectively. Regarding the potential hybrids of M. maximus, a market of 494,471 ha was identified with a commercial value of US$ 94,648,595. The largest market potential is in South Sudan, Ethiopia, and Tanzania with shares of 26.14%, 23.43%, and 22.06%, respectively. The results referred to above suggest that a market for new hybrid forages exists in the region and if other hybrids can be developed. Of course, the development of this market depends on an adequate marketing and dissemination system. In addition, extension programs must promote new technologies to enhance adoption of environmentally compatible new hybrids.